Linguistic and didactic background of foreign bilingual professionally-focused training of future interpreters - Nataliia Voinarovska (Vasyl Stefanyk Precarpathian National University, 2017)
Current article is dedicated to the authentic problems of foreign bilingual professionallyfocusedtraining of future specialists. Pedagogical and linguistic aspects of the process ofdeveloping students' professional and communicative competence within bilingual foreignlanguage teaching fall under analyses in this paper. Theoretical-methodological backgroundsof the concept of bilingual professional teaching and its stages also have become the object ofthe following review. Besides, attributes of favorable bilingual environment, required forlearning activation, are being scrutinized. Therefore, attention is drawn to the nature ofartificial bilingualism (mastering new linguistic-cultural code in the specifically createdenvironment) and obstacles, opposed to a bilingual speaker. Key words: bilingual education, professional training, communicative competence,professional competence, artificial bilingualism, natural bilingualism.